Detection Of Aflatoxin Producing Fungi In Rice And Peanut, And Determination Of Aflatoxin By Hplc-Fld Method (Applied Biological Research, 2023)
Peanut and rice are the widely consumed food material all over the globe. The  contamination of these commodities with aflatoxin is a big challenge and a major health concern. In present study, two aflatoxin producing fungi were  the isolated from rice and peanut and identified as Penicillium charlesii and Aspergillus candidus on the basis of morpho-molecular characteristics A  sensitive, rapid and robust analytical method was developed and validated to  determine the aflatoxin contamination level in aforementioned peanut and rice  matrices. The method involved methanolic extraction of aflatoxin, immune  affinity column clean-up followed by derivatisation with Kobra cell and  fluorescence detection. The analysis of contaminated samples revealed only  two peanut samples and one rice sample possessed aflatoxin B1 and traces of  aflatoxin B2. The method showed 0.05 µg kg-1 as the limit of quantification  which was below the maximum levels set by various global regulations. The  method performance was in line with the performance criteria established by  numerous regulatory bodies such as EU and SANTE.
Keywords: Aflatoxin; HPLC-FLD; identification; peanut; rice